2013
DOI: 10.1094/cchem-02-13-0036-r
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Separation from Ground Corn Flour Using an Electrostatic Method

Abstract: Cereal Chem. 90(6):535-539Corn kernels contain 9% fiber by weight, which is not digested well by nonruminants such as chicken and swine. Also, fiber is nonreactive in the dry-grind process for ethanol production and is considered as feedstock for the production of second-generation bioethanol. Fiber separation can enhance starch concentration in animal feed and increase starch loading in ethanol plants. Electrostatic separation is used to separate particles from granular mixtures under the influence of electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Okada et al. (1986) found that milling the same wheat flour an increased number of times can significantly increase the content of DS. Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…Okada et al. (1986) found that milling the same wheat flour an increased number of times can significantly increase the content of DS. Ma et al.…”
Section: Introductionmentioning
confidence: 99%
“…The second (belt-type coronaelectrostatic separator), akin to a corona drum separator, have been used for removing fibers [6][7], in relatively coarse biomass powder (median size, d50 >1 mm). The present study is aimed at the separation of mineral (silica) and vegetal parts of a raw plant material: rice husk, using a custom-designed corona-electrostatic separator.…”
Section: Introductionmentioning
confidence: 99%